Double-layer polymer dielectric film with interpenetrating interface as well as preparation method and application of double-layer polymer dielectric film
By using a double-layer polymer dielectric film with interpenetrating interface in the dielectric composite material, a ferroelectric polymer and linear dielectric polymer layer are stacked and a heterogeneous molecular interpenetrating interface is constructed, the problem of low dielectric constant and breakdown strength is solved, and the coordinated improvement of high energy storage density and high efficiency is achieved.
Patent Information
- Application Number
- CN202411431650.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-04-25
AI Technical Summary
The dielectric constant and breakdown strength of existing dielectric composite materials are low, making it difficult to effectively improve energy storage density.
A double-layer polymer dielectric film with interpenetration interface is used to stack the ferroelectric polymer layer and the linear dielectric polymer layer, and a heterogeneous molecular interpenetration interface is constructed to regulate the thickness of the interpenetration layer to decouple the inverted coupling relationship between the dielectric constant and the breakdown intensity.
The coordinated improvement of dielectric constant and breakdown strength is achieved, and high energy storage density and high efficiency are obtained at the same time under high electric fields, with an energy density of 22.89J/cm3.
Smart Images

Figure CN119889924A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of energy storage dielectric materials, and in particular to a double-layer polymer dielectric film with an interpenetration interface, and a preparation method and application thereof. Background Art
[0002] Film capacitors are widely used in various electronic and power systems, such as new energy vehicles, electromagnetic pulse weapons, and avionics industries, due to their unique properties, such as high power density, fast charge-discharge speed, long life, high reliability, and easy processing. As the main component of film capacitors, dielectric film materials have attracted extensive research at home and abroad. Although polymer-based dielectric films have high power density, their relatively low energy storage density has become the main factor restricting their further development. The inherent inverse coupling relationship between dielectric constant and breakdown strength is the main reason that hinders the improvement of energy storage density. How to decouple the relationship between the two has become the focus and difficulty of current research.
[0003] Sun et al. prepared ferroelectric / linear dielectric multilayer films by hot pressing and obtained a 12.15 J / cm 3 energy storage density, and a charge-discharge efficiency of 89.9%. Jiang et al. prepared a ferroelectric / linear dielectric multilayer film by electrospinning combined with hot pressing and obtained a breakdown strength of 800MV / m. Although the all-organic ferroelectric / linear dielectric multilayer material has achieved a significant improvement in breakdown strength compared with organic / inorganic composite materials, the improvement in its dielectric constant is not obvious. In addition, under high electric fields, the charge-discharge efficiency of the material is still at a low level. This may be because when preparing multilayer films, only the complementary performance between the macroscopic layers is paid attention to, while the regulation of the two heterogeneous polymers in the interface contact area is ignored, including the solubility of the two polymers, the thickness of the co-infiltration area, etc. In addition, the energy consumption of hot pressing processes, electrospinning processes, etc. is relatively high, which is not conducive to large-scale preparation and industrial production.
[0004] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a double-layer polymer dielectric film with an interpenetration interface and a preparation method and application thereof, aiming to solve the problem of low dielectric constant and breakdown strength of existing dielectric composite materials.
[0006] The technical solution of the present invention is as follows:
[0007] A double-layer polymer dielectric film with an interpenetration interface, comprising a ferroelectric polymer layer and a linear dielectric polymer layer stacked from bottom to top, and an interpenetration layer formed by the mutual penetration of the ferroelectric polymer layer and the linear dielectric polymer layer;
[0008] Or, it is composed of two ferroelectric polymer layers stacked on each other, and an interpenetration layer formed by the two ferroelectric polymer layers penetrating each other;
[0009] Or, it is composed of two linear dielectric polymer layers stacked on each other, and an interpenetration layer formed by the two linear dielectric polymer layers penetrating into each other.
[0010] The double-layer polymer dielectric film with an interpenetrating interface, wherein the material of the ferroelectric polymer layer is selected from poly(vinylidene fluoride), poly(vinylidene fluoride) copolymer or a mixture of two or more poly(vinylidene fluoride) copolymers.
[0011] The double-layer polymer dielectric film with an interpenetration interface, wherein the material of the linear dielectric polymer layer is selected from one of polyetherimide, polyimide, polymethyl methacrylate, and polycarbonate.
[0012] The double-layer polymer dielectric film with an interpenetration interface, wherein the thickness of the interpenetration layer is 50nm-2μm; the thickness of the ferroelectric polymer layer is 2μm-5μm; and the thickness of the linear dielectric polymer layer is 5μm-10μm.
[0013] A method for preparing a double-layer polymer dielectric film with an interpenetration interface comprises the steps of:
[0014] The ferroelectric polymer particles and the linear dielectric polymer particles are mixed with an organic solvent respectively, and subjected to heating and stirring treatment to obtain a ferroelectric polymer solution and a linear dielectric polymer solution;
[0015] Casting the linear dielectric polymer solution or the ferroelectric polymer solution on a substrate, and subjecting it to a shaping treatment to obtain an incompletely dried linear dielectric polymer layer or ferroelectric polymer layer;
[0016] The ferroelectric polymer solution or the linear dielectric polymer solution is cast on the incompletely dried linear dielectric polymer layer or the ferroelectric polymer layer, and subjected to gradient temperature increase treatment and quenching treatment to obtain a double-layer polymer dielectric film with an interpenetration interface.
[0017] The method for preparing a double-layer polymer dielectric film with an interpenetration interface, wherein the concentration of the ferroelectric polymer solution is 0.1g / ml-0.4g / ml; the concentration of the linear dielectric polymer solution is 0.1g / ml-0.4g / ml.
[0018] The method for preparing a double-layer polymer dielectric film with an interpenetration interface, wherein the temperature of the heating and stirring treatment is 40° C.-90° C., and the time of the heating and stirring treatment is 12 h-24 h.
[0019] The method for preparing a double-layer polymer dielectric film with an interpenetration interface, wherein the temperature of the shaping treatment is 50° C.-100° C., and the time of the shaping treatment is 30 min-60 min.
[0020] The method for preparing a double-layer polymer dielectric film with an interpenetration interface, wherein the gradient temperature increase treatment includes: heating from room temperature to 80°C-120°C at a heating rate of 1°C / min-5°C / min and keeping warm for 3h-4h, then continuing to heat to 160°C-220°C at a heating rate of 5°C / min-10°C / min and keeping warm for 4min-6min; the quenching treatment is carried out in ice water.
[0021] A double-layer polymer dielectric film with an interpenetrating interface is used in film capacitors.
[0022] Beneficial effects: The present invention provides a double-layer polymer dielectric film with an interpenetration interface and a preparation method and application thereof. The double-layer polymer dielectric film with an interpenetration interface includes a ferroelectric polymer layer and a linear dielectric polymer layer, and an interpenetration layer formed by the mutual penetration of the ferroelectric polymer layer and the linear dielectric polymer layer; or, an interpenetration layer formed by two layers of the ferroelectric polymer layer stacked on each other and two layers of the ferroelectric polymer layer interpenetrated on each other; or, an interpenetration layer formed by two layers of the linear dielectric polymer layer stacked on each other and two layers of the linear dielectric polymer layer interpenetrated on each other. The present invention utilizes ferroelectric polymer layers and / or linear dielectric polymer layers for stacking, and by constructing a heterogeneous molecular interpenetration interface between the ferroelectric polymer layers and / or the linear dielectric polymer layers as an interpenetration layer, the inverted coupling relationship between the dielectric constant and the breakdown strength can be effectively decoupled, and the synergistic improvement of the dielectric constant and the breakdown strength can be achieved; and, by regulating the thickness of the heterogeneous molecular interpenetration interface between the ferroelectric polymer layers and / or the linear dielectric polymer layers, a high dielectric constant and a breakdown strength can be simultaneously obtained. Secondly, the improvement in dielectric constant is due to the polar phase transition of ferroelectric polymer induced by linear dielectric polymer in the interpenetration layer; the improvement in breakdown strength is due to the enhanced interaction between linear dielectric molecular chains and ferroelectric polymer molecular chains in the interpenetration layer, while the improvement in efficiency and energy storage density is due to the increase in deep trap density in the interpenetration layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 A schematic diagram of the structure of a double-layer polymer dielectric film with an interpenetrating interface;
[0024] Figure 2 It is a process flow diagram of a method for preparing a double-layer polymer dielectric film with an interpenetration interface according to the present invention;
[0025] Figure 3 is the AFM-IR spectrum of the double-layer polymer dielectric film prepared in Example 1;
[0026] Figure 4 The discharge energy density and efficiency data of the double-layer polymer dielectric film prepared in Example 1 are shown in FIG.
[0027] Figure 5 is the AFM-IR spectrum of the double-layer polymer dielectric film prepared in Example 4;
[0028] Figure 6 is the AFM-IR spectrum of the double-layer polymer dielectric film prepared in Example 5;
[0029] Figure 7 The dielectric constant and dielectric loss data of PEI-based, PMMA-based and PI-based double-layer polymers are shown in the figure;
[0030] Figure 8 The breakdown strength data of PEI-based, PMMA-based and PI-based double-layer polymers are shown in Figure 2.
[0031] Fig. 9 The dielectric constant and breakdown strength data of the double-layer polymer dielectric film prepared in Example 6;
[0032] Fig.10 The dielectric constant and breakdown strength data of the double-layer polymer dielectric film prepared in Example 7 are shown in FIG. DETAILED DESCRIPTION
[0033] The present invention provides a double-layer polymer dielectric film with an interpenetration interface and a preparation method and application thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0034] It will be understood by those skilled in the art that, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as generally understood by those skilled in the art in the art to which the present invention belongs. It should also be understood that terms such as those defined in general dictionaries should be understood to have meanings consistent with the meanings in the context of the prior art, and will not be interpreted with idealized or overly formal meanings unless specifically defined as herein.
[0035] In recent years, although the organic / inorganic nano composite material prepared by combining nano ceramic filler with high dielectric constant with polymer composite can effectively improve dielectric constant, the processing properties of material are reduced due to the introduction of inorganic filler. In addition, ceramic filler is easily reunited in polymer matrix, which makes dielectric loss sharply increase, and breakdown strength significantly reduces. Although the breakdown strength of material can be improved to a certain extent by building the organic / inorganic composite material of multilayer structure, the phenomenon that charge-discharge efficiency is low is ubiquitous. And along with the increase of number of plies, defects are increased, and the processing properties of material are greatly reduced.
[0036] Constructing all-organic polymer composites can avoid the negative effects caused by filler agglomeration and effectively reduce the dielectric loss of the material. However, due to the low dielectric constant of the linear dielectric polymer itself, the polarization improvement of multilayer linear dielectric polymer materials is limited, and the improvement of energy storage density is also extremely limited. Ferroelectric polymers have high dielectric constants, and combining them with linear dielectrics with low dielectric constants to prepare blended single-layer or multi-layer polymer composites has become a new research direction. However, the dielectric constant and breakdown strength of existing dielectric composites are still relatively low and cannot be well applied.
[0037] Based on this, Figure 1 As shown, the present invention provides a double-layer polymer dielectric film with an interpenetration interface, comprising a ferroelectric polymer layer 10 and a linear dielectric polymer layer 20, and an interpenetration layer 30 formed by the mutual penetration of the ferroelectric polymer layer 10 and the linear dielectric polymer layer 20;
[0038] Or, it is composed of two ferroelectric polymer layers 10 stacked on each other, and an interpenetration layer 30 formed by the two ferroelectric polymer layers 10 penetrating each other;
[0039] Or, it is composed of two linear dielectric polymer layers 20 stacked on each other, and an interpenetration layer 30 formed by the two linear dielectric polymer layers 20 penetrating into each other.
[0040] In this embodiment, ferroelectric polymer layers and / or linear dielectric polymer layers are stacked, and a heterogeneous molecular interpenetration interface between the ferroelectric polymer layers and / or the linear dielectric polymer layers is constructed as an interpenetration layer, so that the inverted coupling relationship between the dielectric constant and the breakdown strength can be effectively decoupled, thereby achieving a synergistic improvement in the dielectric constant and the breakdown strength; and, by regulating the thickness of the heterogeneous molecular interpenetration interface between the ferroelectric polymer layers and / or the linear dielectric polymer layers, a high dielectric constant and a breakdown strength can be obtained simultaneously.
[0041] Secondly, the dielectric constant of the double-layer polymer dielectric film obtained by stacking a ferroelectric polymer layer and a linear dielectric polymer layer is improved due to the linear dielectric polymer inducing the polar phase transition of the ferroelectric polymer in the interpenetration layer; the breakdown strength is improved due to the enhanced interaction between the linear dielectric molecular chains and the ferroelectric polymer molecular chains in the interpenetration layer, while the efficiency and energy storage density are improved due to the increase in the deep trap density in the interpenetration layer.
[0042] Specifically, the double-layer polymer dielectric film with an interpenetrating interface provided by the present invention achieves a synergistic improvement in dielectric constant and breakdown strength, and can simultaneously obtain high energy storage density and high efficiency under high electric field. When the efficiency is ≥90%, 22.89 J / cm 3 energy density.
[0043] In some embodiments, the material of the ferroelectric polymer layer is selected from but not limited to poly(vinylidene fluoride) (PVDF), poly(vinylidene fluoride) copolymers, or a mixture of two or more poly(vinylidene fluoride) copolymers.
[0044] In some embodiments, the poly(vinylidene fluoride) copolymer includes but is not limited to one or more of poly(vinylidene fluoride-hexafluoropropylene) (P(VDF-HFP)), poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene) (P(VDF-TrFE-CFE)); the mixture of two or more poly(vinylidene fluoride) copolymers can be selected from but is not limited to the mixture of poly(vinylidene fluoride-hexafluoropropylene) and poly(vinylidene fluoride-trifluoroethylene-chlorofluoroethylene).
[0045] In some embodiments, the material of the linear dielectric polymer layer is selected from but not limited to one of polyetherimide (PEI), polyimide (PI), polymethyl methacrylate (PMMA), and polycarbonate (PC).
[0046] In some embodiments, the thickness of the interpenetration layer is 50nm-2μm; the thickness of the ferroelectric polymer layer is 2μm-5μm; the thickness of the linear dielectric polymer layer is 5μm-10μm. By constructing a heterogeneous molecular interpenetration interface between ferroelectric polymers and / or linear dielectric polymers and controlling the thickness of the interpenetration layer to be between 50nm-2μm, the inverted coupling relationship between the dielectric constant and the breakdown strength can be effectively decoupled, and the synergistic improvement of the dielectric constant and the breakdown strength can be achieved; and by regulating the thickness of the heterogeneous molecular interpenetration interface between the ferroelectric polymers and / or linear dielectric polymers, a high dielectric constant and a breakdown strength can be obtained simultaneously.
[0047] In some embodiments, the ratio of the thickness of the linear dielectric polymer layer to the thickness of the ferroelectric polymer layer is (5-8):(2-5); by way of example, the ratio of the thickness of the linear dielectric polymer layer to the thickness of the ferroelectric polymer layer can be 8:2, 7:3, 6:4 and 5:5.
[0048] In a preferred embodiment, the ratio of the thickness of the linear dielectric polymer layer to the thickness of the ferroelectric polymer layer is 7:3.
[0049] In addition, Figure 2 As shown, the present invention also provides a method for preparing a double-layer polymer dielectric film with an interpenetration interface, comprising the steps of:
[0050] Step S10: mixing the ferroelectric polymer particles and the linear dielectric polymer particles with an organic solvent respectively, and subjecting the mixture to heating and stirring to obtain a ferroelectric polymer solution and a linear dielectric polymer solution;
[0051] Step S20: casting the linear dielectric polymer solution or the ferroelectric polymer solution on a substrate, and subjecting the solution to a shaping treatment to obtain a linear dielectric polymer layer or a ferroelectric polymer layer that is not completely dried;
[0052] Step S30: casting the ferroelectric polymer solution or the linear dielectric polymer solution on the incompletely dried linear dielectric polymer layer or ferroelectric polymer layer, and subjecting the layer to gradient temperature rise treatment and quenching treatment to obtain a double-layer polymer dielectric film with an interpenetration interface.
[0053] In this embodiment, a double-layer polymer dielectric film with an interpenetration interface can be prepared by an improved casting process, and the thickness of the interpenetration layer can also be controlled by adjusting the parameters of the preparation process. Compared with the film prepared by the traditional casting process, the present invention can regulate the thickness and type of the interlayer molecular co-penetration interface; compared with the film prepared by the hot pressing process, the operation steps are simpler and the energy consumption is lower; compared with the film prepared by the electrospinning process, the preparation process is simpler, the controllability is higher, and the energy consumption is lower; compared with the film prepared by the spin coating process, the operation steps are simpler, easy to prepare on a large scale, and the controllability is higher.
[0054] Specifically, the double-layer film prepared by the present invention achieves a synergistic improvement in dielectric constant and breakdown strength, and simultaneously obtains high energy storage density and high efficiency under high electric field. When the efficiency is ≥90%, 22.89 J / cm 3 Furthermore, the improvement of dielectric constant is due to the polar phase transition of ferroelectric polymer induced by linear dielectric polymer in the interpenetration layer; the improvement of breakdown strength is due to the enhanced interaction between linear dielectric molecular chains and ferroelectric polymer molecular chains in the interpenetration layer, while the improvement of efficiency and energy storage density is due to the increase of deep trap density in the interpenetration layer.
[0055] In some embodiments, the concentration of the ferroelectric polymer solution is 0.1 g / ml-0.4 g / ml; the concentration of the linear dielectric polymer solution is 0.1 g / ml-0.4 g / ml. By controlling the concentration of the ferroelectric polymer solution and the concentration of the linear dielectric polymer solution within the above range, the thickness of the interpenetration layer can be precisely controlled, and the obtained double-layer polymer dielectric film has a high dielectric constant and breakdown strength.
[0056] In a preferred embodiment, the concentration of the ferroelectric polymer solution is 0.2 g / ml; the concentration of the linear dielectric polymer solution is 0.2 g / ml.
[0057] In some embodiments, the temperature of the heating and stirring treatment is 40°C-90°C, the time of the heating and stirring treatment is 12h-24h, and the heating and stirring treatment is carried out by magnetic stirring. A uniformly dispersed ferroelectric polymer solution and a linear dielectric polymer solution can be obtained by the heating and stirring treatment. Under such conditions, the heating and stirring treatment can be carried out to obtain a uniformly dispersed ferroelectric polymer solution and a linear dielectric polymer solution while saving time and energy.
[0058] In some embodiments, the temperature of the shaping treatment is 50°C-100°C, and the time of the shaping treatment is 30min-60min. The shaping treatment under this condition can obtain a linear dielectric polymer layer in which the solvent is not completely volatilized, that is, a linear dielectric polymer layer in an incompletely dried state is obtained, which is convenient for the subsequent formation of an interpenetration interface. In traditional double-layer materials, after the first layer is cast, the second casting will be performed after the solvent of the first layer is completely volatilized to obtain the first layer in a dry state; the present invention casts a linear dielectric polymer solution on a clean glass plate with a thickness of about 5-8 microns, places the glass plate in a vacuum oven, and dries it at 50°C-100°C for 30-60min. Short-term drying allows the polymer to be shaped, and the solvent is not completely volatilized, which is convenient for the subsequent formation of an interpenetration interface. Under this shaping treatment temperature and time, the organic solvent in the linear dielectric polymer layer can be not completely volatilized, and a linear dielectric polymer layer that is not completely dried can be obtained, which is convenient for the subsequent formation of an interpenetration interface.
[0059] In some embodiments, the gradient temperature rise treatment includes: heating from room temperature to 80°C-120°C at a heating rate of 1°C / min-5°C / min and keeping the temperature for 3h-4h, and then continuing to heat to 160°C-220°C at a heating rate of 5°C / min-10°C / min and keeping the temperature for 4min-6min; the quenching treatment is performed in ice water. Slow heating can form an interpenetration layer, and adjusting the heating time and temperature can regulate the thickness of the interpenetration layer; and the gradient temperature rise and quenching treatment can promote the formation of the polar phase of the ferroelectric polymer.
[0060] In some embodiments, after step S30, the film that has undergone gradient temperature increase treatment and quenching treatment is placed in a forced air oven and kept at 60° C. for 2 to 10 hours; and the film is dried to remove residual solvent and moisture to obtain a dry double-layer polymer dielectric film with an interpenetration interface.
[0061] In addition, the present invention also provides an application of a double-layer polymer dielectric film with an interpenetration interface in a film capacitor.
[0062] In this embodiment, the double-layer polymer dielectric film with an interpenetrating interface achieves a synergistic improvement in dielectric constant and breakdown strength, and can simultaneously obtain high energy storage density and high efficiency under high electric field. When the efficiency is ≥90%, 22.89 J / cm 3 energy density.
[0063] The following examples are further given to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention.
[0064] Example 1
[0065] This embodiment provides a double-layer polymer dielectric film, one layer is a ferroelectric polymer blend layer P(VDF-HFP) / P(VDF-TrFE-CFE), and the other layer is a linear dielectric polymer PEI layer. The thickness of the heterogeneous molecular interpenetration interface is about 500nm. The preparation process includes:
[0066] 1) P(VDF-HFP) particles and P(VDF-TrFE-CFE) powder were weighed in a mass ratio of 3:2 and dissolved in NMP solution (2 g solute / 10 ml solution), and magnetically stirred at 50-80° C. for 8-16 h to obtain a P(VDF-HFP) / P(VDF-TrFE-CFE) blend solution; 2 g PEI particles were dissolved in 10 ml NMP solution, and magnetically stirred at 50-80° C. for 8-16 h to obtain a PEI solution.
[0067] 2) First, cast the PEI solution on a clean glass plate, place the glass plate in a vacuum oven, and dry it at 60-90° C. for 20-60 min.
[0068] 3) Cast the P(VDF-HFP) / P(VDF-TrFE-CFE) blend solution on the first PEI layer. Place the glass plate in a forced air oven, heat it from room temperature to 100°C at a heating rate of 0.5-3°C / min, and keep it warm for 2-6 hours; heat it from 100°C to 200°C at a heating rate of 0.5-3°C / min, and keep it warm for 3-10 minutes, then immediately place it in ice water and peel off the film.
[0069] 4) placing the film in a forced air oven at 50-80° C. for 8-16 hours to obtain a double-layer polymer dielectric film.
[0070] The AFM-IR spectrum of the double-layer polymer dielectric film prepared in this example is as follows: Figure 3 As shown in the figure, it can be seen that the thickness of the molecular interpenetration interface is about 500nm.
[0071] The discharge energy density and efficiency data of the double-layer polymer dielectric film prepared in this embodiment are shown in the figure Figure 4 As shown in the figure, it can be seen that the double-layer film prepared in this embodiment has high charge-discharge efficiency and high energy storage density.
[0072] Example 2
[0073] This embodiment provides a double-layer polymer dielectric film, one layer is a ferroelectric polymer blend layer P(VDF-HFP) / P(VDF-TrFE-CFE), and the other layer is a linear dielectric polymer PMMA. The preparation process includes:
[0074] 1) P(VDF-HFP) particles and P(VDF-TrFE-CFE) powder were weighed in proportion (60wt%) and dissolved in NMP solution, and magnetically stirred at 50-80°C for 8-16h to obtain P(VDF-HFP) / P(VDF-TrFE-CFE) blend solution (2g / 10ml); PEI particles were dissolved in NMP solution, and magnetically stirred at 50-80°C for 8-16h to obtain PMMA solution (2g / 10ml).
[0075] 2) First, PMMA solution (2 g / 10 ml) was cast onto a clean glass plate, and the glass plate was placed in a vacuum oven and dried at 60-90° C. for 20-60 min.
[0076] 3) Cast the P(VDF-HFP) / P(VDF-TrFE-CFE) blend solution (2g / 10ml) on the first PMMA (2g / 10ml) layer. Place the glass plate in a forced air oven, heat it from room temperature to 100°C at a heating rate of 0.5-3°C / min, and keep it warm for 2-6h; heat it from 100°C to 200°C at a heating rate of 0.5-3°C / min, and keep it warm for 3-10min, then immediately place it in ice water and peel off the film.
[0077] 4) placing the film in a forced air oven at 50-80° C. for 8-16 hours to obtain a double-layer polymer dielectric film.
[0078] Example 3
[0079] This embodiment provides a double-layer polymer dielectric film, one layer is a ferroelectric polymer blended layer P(VDF-HFP) / P(VDF-TrFE-CFE), and the other layer is a linear dielectric polymer PI, and the preparation process thereof includes:
[0080] 1) P(VDF-HFP) particles and P(VDF-TrFE-CFE) powder were weighed in proportion (60wt%) and dissolved in NMP solution, and magnetically stirred at 50-80°C for 5-16h to obtain P(VDF-HFP) / P(VDF-TrFE-CFE) blend solution (2g / 10ml); PI particles were dissolved in NMP solution, and magnetically stirred at 50-80°C for 5-16h to obtain PI solution (2g / 10ml).
[0081] 2) First, cast the PI solution (2 g / 10 ml) on a clean glass plate, and then place the glass plate in a vacuum oven and dry it at 60-90° C. for 20-60 min.
[0082] 3) Cast the P(VDF-HFP) / P(VDF-TrFE-CFE) blend solution (2g / 10ml) on the first PI layer. Place the glass plate in a forced air oven, heat it from room temperature to 100°C at a heating rate of 0.5-3°C / min, and keep it warm for 2-6h; heat it from 100°C to 200°C at a heating rate of 0.5-3°C / min, and keep it warm for 3-10min, then immediately place it in ice water and peel off the film.
[0083] 4) placing the film in a forced air oven at 50-80° C. for 8-16 hours to obtain a double-layer polymer dielectric film.
[0084] Example 4
[0085] This embodiment provides a double-layer polymer dielectric film, one layer is a ferroelectric polymer blend layer P(VDF-HFP) / P(VDF-TrFE-CFE), and the other layer is a linear dielectric polymer PEI. The thickness of the heterogeneous molecular interpenetration interface is about 300nm. The preparation process includes:
[0086] 1) P(VDF-HFP) particles and P(VDF-TrFE-CFE) powder were weighed in proportion and dissolved (60wt%) in a solution of NMP and acetone in a ratio of 1:1, and magnetically stirred at room temperature for 8 to 16 hours to obtain a P(VDF-HFP) / P(VDF-TrFE-CFE) blend solution (2g / 10ml); PEI particles were dissolved in the NMP solution, and magnetically stirred at 50 to 80°C for 8 to 16 hours to obtain a PEI solution (2g / 10ml).
[0087] 2) First, cast the PEI solution (2 g / 10 ml) on a clean glass plate, and then place the glass plate in a vacuum oven and dry it at 60-100° C. for 1-3 h.
[0088] 3) Cast the P(VDF-HFP) / P(VDF-TrFE-CFE) blend solution (2g / 10ml) on the first PEI layer. Place the glass plate in a forced air oven, heat it from room temperature to 100°C at a heating rate of 0.5-3°C / min, and keep it warm for 2-6h; heat it from 100°C to 200°C at a heating rate of 0.5-3°C / min, and keep it warm for 3-10min, then immediately place it in ice water and peel off the film.
[0089] 4) placing the film in a forced air oven at 50-80° C. for 8-12 hours to obtain a double-layer polymer dielectric film.
[0090] The AFM-IR image of the double-layer polymer dielectric film prepared in this example is as follows: Figure 5 As shown in the figure, the molecular interpenetration interface thickness is about 300nm. Figure 5 a and b in the figure are the morphology image of the film cross section under atomic force microscopy and Fourier infrared image, respectively.
[0091] Example 5
[0092] This embodiment provides a double-layer polymer dielectric film, one layer is a ferroelectric polymer blend layer P(VDF-HFP) / P(VDF-TrFE-CFE), and the other layer is a linear dielectric polymer PEI. The thickness of the heterogeneous molecular interpenetration interface is about 800nm. The preparation process includes:
[0093] 1) P(VDF-HFP) particles and P(VDF-TrFE-CFE) powder were weighed in proportion (60wt%) and dissolved in NMP solution, and magnetically stirred at 50-80°C for 8-16h to obtain P(VDF-HFP) / P(VDF-TrFE-CFE) blend solution (2g / 10ml); PEI particles were dissolved in NMP solution, and magnetically stirred at 50-80°C for 8-16h to obtain PEI solution (2g / 10ml).
[0094] 2) First, cast the PEI solution (2 g / 10 ml) on a clean glass plate, and then place the glass plate in a vacuum oven and dry it at 40-80° C. for 20-60 min.
[0095] 3) Cast the P(VDF-HFP) / P(VDF-TrFE-CFE) blend solution (2g / 10ml) on the first PEI layer. Place the glass plate in a forced air oven, heat it from room temperature to 100°C at a heating rate of 0.5-3°C / min, and keep it warm for 2-6h; heat it from 100°C to 200°C at a heating rate of 0.5-3°C / min, and keep it warm for 3-10min, then immediately place it in ice water and peel off the film.
[0096] 4) placing the film in a forced air oven at 50-80° C. for 8-12 hours to obtain a double-layer polymer dielectric film.
[0097] The AFM-IR image of the double-layer polymer dielectric film prepared in this example is as follows: Figure 6 As shown in the figure, the molecular interpenetration interface thickness is about 800nm. Figure 6 a and b in the figure are the morphology image of the film cross section under atomic force microscopy and Fourier infrared image, respectively.
[0098] The dielectric constant and dielectric loss data of PEI-based, PMMA-based and PI-based double-layer polymers are shown in the figure below. Figure 7 As shown, Figure 7 a, b, and c in the figure correspond to the double-layer polymer dielectric films obtained by the PEI-based film of Example 1, the PMMA-based film of Example 2, and the PI-based film of Example 3, respectively; it can be seen from the figure that the design of the heterogeneous molecular interpenetration interface enables the dielectric constant and dielectric loss to be synergistically improved. The breakdown strength data of the double-layer polymers based on PEI, PMMA, and PI are shown in the figure. Figure 8 As shown, a, b, and c correspond to the double-layer polymer dielectric films obtained by the PEI base of Example 1, the PMMA base of Example 2, and the PI base of Example 3, respectively. It can be seen from the figure that the design of the heterogeneous molecular interpenetration interface enables the breakdown strength to be synergistically improved.
[0099] Example 6
[0100] This embodiment provides a double-layer polymer dielectric film, one layer is a linear dielectric polymer PEI, and the other layer is a linear dielectric polymer PC.
[0101] The preparation process includes:
[0102] 1) PEI and PC particles were dissolved in NMP solution respectively, and magnetic stirring was performed at 50-80° C. for 8-16 h to obtain PEI solution and PC solution (2 g / 10 ml), respectively.
[0103] 2) First, cast the PEI solution (2 g / 10 ml) on a clean glass plate, and then place the glass plate in a vacuum oven and dry it at 60-100° C. for 1-3 h.
[0104] 3) Cast the PC solution (2g / 10ml) on the first PEI layer. Place the glass plate in a forced air oven, heat it from room temperature to 100°C at a heating rate of 0.5-3°C / min, and keep it warm for 2-6 hours; heat it from 100°C to 200°C at a heating rate of 0.5-3°C / min, and keep it warm for 3-10 minutes, then immediately place it in ice water and peel off the film.
[0105] 4) placing the film in a forced air oven at 50-80° C. for 8-12 hours to obtain a double-layer polymer dielectric film.
[0106] The dielectric constant and breakdown strength of the double-layer polymer dielectric film prepared in this embodiment are as follows: Fig. 9 As shown. Among them, Fig. 9 Where a is the dielectric constant and b is the breakdown strength.
[0107] Example 7
[0108] This embodiment provides a double-layer polymer dielectric film, one layer is a ferroelectric polymer PVDF, and the other layer is a ferroelectric polymer P (VDF-HFP).
[0109] The preparation process includes:
[0110] 1) PVDF and P (VDF-HFP) particles were dissolved in NMP solution respectively, and magnetically stirred at 50-80° C. for 8-16 h to obtain PVDF solution and P (VDF-HFP) solution (2 g / 10 ml), respectively.
[0111] 2) First, cast the PVDF solution (2 g / 10 ml) on a clean glass plate, and then place the glass plate in a vacuum oven and dry it at 60-100° C. for 1-3 h.
[0112] 3) Cast the P(VDF-HFP) solution (2g / 10ml) on the first PVDF layer. Place the glass plate in a forced air oven, and heat it from room temperature to 100°C at a heating rate of 0.5-3°C / min, and keep it warm for 2-6 hours; heat it from 100°C to 200°C at a heating rate of 0.5-3°C / min, and keep it warm for 3-10 minutes, then immediately place it in ice water and peel off the film.
[0113] 4) placing the film in a forced air oven at 50-80° C. for 8-12 hours to obtain a double-layer polymer dielectric film.
[0114] The dielectric constant and breakdown strength of the double-layer polymer dielectric film prepared in this embodiment are as follows: Fig.10 As shown. Among them, Fig.10 Where a is the dielectric constant and b is the breakdown strength.
[0115] In summary, the present invention provides a double-layer polymer dielectric film with an interpenetration interface and a preparation method and application thereof. The double-layer polymer dielectric film with an interpenetration interface includes a ferroelectric polymer layer and a linear dielectric polymer layer, and an interpenetration layer formed by the mutual penetration of the ferroelectric polymer layer and the linear dielectric polymer layer; or, it is composed of two layers of the ferroelectric polymer layers stacked on each other, and an interpenetration layer formed by the mutual penetration of the two ferroelectric polymer layers; or, it is composed of two layers of the linear dielectric polymer layers stacked on each other, and an interpenetration layer formed by the mutual penetration of the two linear dielectric polymer layers. The present invention utilizes ferroelectric polymer layers and / or linear dielectric polymer layers for stacking, and by constructing a heterogeneous molecular interpenetration interface between the ferroelectric polymer layers and / or the linear dielectric polymer layers as an interpenetration layer, it can effectively decouple the inverted coupling relationship between the dielectric constant and the breakdown strength, and realize the synergistic improvement of the dielectric constant and the breakdown strength; and by regulating the thickness of the heterogeneous molecular interpenetration interface between the ferroelectric polymer layers and / or the linear dielectric polymer layers, a high dielectric constant and a breakdown strength can be obtained at the same time. Secondly, the improvement in dielectric constant is due to the polar phase transition of ferroelectric polymer induced by linear dielectric polymer in the interpenetration layer; the improvement in breakdown strength is due to the enhanced interaction between linear dielectric molecular chains and ferroelectric polymer molecular chains in the interpenetration layer, while the improvement in efficiency and energy storage density is due to the increase in deep trap density in the interpenetration layer.
[0116] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A double-layer polymer dielectric film having an interpenetrating interface, characterized in that: The invention comprises a ferroelectric polymer layer and a linear dielectric polymer layer stacked from bottom to top, and an interpenetration layer formed by the mutual penetration of the ferroelectric polymer layer and the linear dielectric polymer layer; Or, it is composed of two ferroelectric polymer layers stacked on each other, and an interpenetration layer formed by the two ferroelectric polymer layers penetrating each other; Or, it is composed of two linear dielectric polymer layers stacked on each other, and an interpenetration layer formed by the two linear dielectric polymer layers penetrating into each other.
2. The double-layer polymer dielectric film with an interpenetration interface according to claim 1, characterized in that: The material of the ferroelectric polymer layer is selected from poly(vinylidene fluoride), poly(vinylidene fluoride) copolymer or a mixture of two or more poly(vinylidene fluoride) copolymers.
3. The double-layer polymer dielectric film with an interpenetration interface according to claim 1, characterized in that: The material of the linear dielectric polymer layer includes, but is not limited to, one of polyetherimide, polyimide, polymethyl methacrylate, and polycarbonate.
4. The double-layer polymer dielectric film with an interpenetration interface according to claim 1, characterized in that: The thickness of the interpenetration layer is 50 nm-2 μm; the thickness of the ferroelectric polymer layer is 2 μm-5 μm; and the thickness of the linear dielectric polymer layer is 5 μm-10 μm.
5. A method for preparing a double-layer polymer dielectric film having an interpenetration interface as claimed in any one of claims 1 to 4, characterized in that: Includes steps: The ferroelectric polymer particles and the linear dielectric polymer particles are mixed with an organic solvent respectively, and subjected to heating and stirring treatment to obtain a ferroelectric polymer solution and a linear dielectric polymer solution; Casting the linear dielectric polymer solution or the ferroelectric polymer solution on a substrate, and subjecting it to a shaping treatment to obtain an incompletely dried linear dielectric polymer layer or ferroelectric polymer layer; The ferroelectric polymer solution or the linear dielectric polymer solution is cast on the incompletely dried linear dielectric polymer layer or the ferroelectric polymer layer, and subjected to gradient temperature increase treatment and quenching treatment to obtain a double-layer polymer dielectric film with an interpenetration interface.
6. The method for preparing a double-layer polymer dielectric film with an interpenetration interface according to claim 5, characterized in that: The concentration of the ferroelectric polymer solution is 0.1 g / ml-0.4 g / ml; the concentration of the linear dielectric polymer solution is 0.1 g / ml-0.4 g / ml.
7. The method for preparing a double-layer polymer dielectric film with an interpenetration interface according to claim 5, characterized in that: The temperature of the heating and stirring treatment is 40° C.-90° C., and the time of the heating and stirring treatment is 12 h-24 h.
8. The method for preparing a double-layer polymer dielectric film with an interpenetration interface according to claim 5, characterized in that: The temperature of the shaping treatment is 50° C.-100° C., and the time of the shaping treatment is 30 min-60 min.
9. The method for preparing a double-layer polymer dielectric film with an interpenetration interface according to claim 5, characterized in that: The gradient temperature rise treatment includes: heating from room temperature to 80°C-120°C at a heating rate of 1°C / min-5°C / min and keeping warm for 3h-4h, then continuing to heat to 160°C-220°C at a heating rate of 5°C / min-10°C / min and keeping warm for 4min-6min; the quenching treatment is carried out in ice water.
10. Use of the double-layer polymer dielectric film with an interpenetration interface as claimed in any one of claims 1 to 4 in a film capacitor.